PAI Teachers' Efforts To Increase Online Learning Creativity During The Covid-19 Pandemic - Sopiatunisa Sopiatunisa (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
This study aims to determine how Islamic education teachers are trying to improve online learning creativity during the Covid-19 pandemic at SMPN 1 Pamijahan Bogor in 2021. This research is a type of field research with qualitative methods. The results showed that Islamic education teachers at SMPN 1 Pamijahan Bogor had creativity in the implementation of online learning, this form of creativity can be seen from: (1) the teachers strives to always build students' enthusiasm by providing motivation every time they start learning. (2) the teachers uses the appropriate media with the material to be studied. (3) the teachers uses the teaching material. (4) teachers are able to overcome learning difficulties and problems that occur during online learning. (5) the teachers uses a method that is in accordance with the existing situation and conditions. (6) the teachers prepares an evaluation at the end of the lesson. Some of the things that have been done by islamic education teachers at SMPN 1 Pamijahan Bogor are included in the indicators of creative teachers even though they are not fully maksimal, islamic education teachers are quite creative in carrying out online learning despite the various challenges and problems that occur.